Penerapan Pendekatan Metakognitif untuk Meningkatkan Kemampuan Siswa Kelas V SD dalam Memodelkan Soal Cerita Matematika - Nur‘Afifah Nur‘Afifah (Departement of Mathematics Education, 2022)
This research is motivated by the low ability to solve elementary math word problems. This is because students are less accustomed to solving math word problems. The formulation of the research problem is whether the application of the PQ4R metacognitive approach can be used to reveal the ability of fifth grade elementary school students in modeling math word problems on the subject of fractions? and is there an increase in the ability of fifth grade elementary school students in modeling math word problems on the subject of fractions through the application of the PQ4R metacognitive approach? The purpose of this study was to identify the application of the PQ4R metacognitive approach and to determine the increase in the ability of fifth grade elementary school students in modeling math word problems on the subject of fractions through the application of the PQ4R metacognitive approach. This research began with the development of a metacognitive approach in terms of the development of Learning Implementation Plans, aids (in the form of teaching materials and LAS), math questions in the form of word problems and instrument trials. The research subjects were 47 VA class students. The results showed that the application of the PQ4R metacognitive approach could be used to reveal the ability of fifth grade elementary school students in modeling math word problems on the subject of fractions from observations of learning management in cycle I and cycle II which were in the good category, the observation results the teacher's activities in the first cycle were in the good category and in the second cycle they were very good, the results of observations of student activities in the first cycle were in the sufficient category and in the second cycle they were very good; and the ability of fifth grade elementary school students in modeling math word problems on the subject of fractions through the application of the PQ4R metacognitive approach has increased